Effect of high-intensity anaerobic exercise on electrocortical activity in athletes and non-athletes - Costa, É.; Gongora, M.; Bittencourt, J.; Marinho, V.; Cagy, M.; Teixeira, S.; Nicoliche, E.; Fernandes, I.; Fagundes, D.; Machado, C.; Dias, J.; Vicente, R.; et al. (PLOS ONE, 2025)
Aim The present study aims to verify the information processing in athletes through electroencephalography, analyze cortical areas responsible for cognitive functions related to attentional processing of visual stimuli, and investigate motor activity`s influence on cognitive aspects. Additionally, we aimed to analyze the acute effect of physical exercise after the high-intensity anaerobic effort, evaluating how a short-duration Wingate test influences cortical activity and attentional processing immediately following exertion.